1990
DOI: 10.1172/jci114445
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibronectin in Pneumocystis carinii attachment to cultured lung cells.

Abstract: Attachment of pathogens to host cells is a prerequisite for the development of many infections. Pneumocystis cainfif (PC) pneumonia is characterized by attachment of PC trophozoites to the alveolar epithelium. The mechanism of this process is unknown. Fibronectin (Fn) is a glycoprotein present in the alveolar space known to mediate cell-cell attachment, including the attachment of certain pathogens to host epithelial cells. In this study the binding of Fn to PC trophozoites has been characterized in vitro u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 43 publications
7
77
0
Order By: Relevance
“…Previous work from our laboratory has demonstrated that Fn binding to P. carinji organisms is a saturable and specific process that is essential for optimal P. carinii attachment (13).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Previous work from our laboratory has demonstrated that Fn binding to P. carinji organisms is a saturable and specific process that is essential for optimal P. carinii attachment (13).…”
Section: Resultsmentioning
confidence: 95%
“…carinii attachment assay. As previously described (13,21), P. carinii attachment to an alveolar epithelial cell line was quantified using 5"Cr-labeled P. carinii organisms. Freshly isolated P. carinii trophozoites were incubated for 18 h in 2 ml of DME containing 0.5 ml of FCS and 50 MCi of 5"Cr sodium chromate (New England Nuclear, Boston, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this fungus does not invade these cells to any significant degree and intracellular fungi are observed only within macrophages and granulocytes (Hoyte et al 1997;Limper et al 1997). The adherence of P. jirovecii to epithelial cells is mediated through the binding of the extracellular macromolecules fibronectin and vitronectin, which serve as bridging molecules linking the fungus to host cells (Pottratz and Martin 1990b;Pottratz et al 1991Pottratz et al , 1994Limper et al 1993). Vitronectin and fibronectin both interact with b-glucans on the surface of the fungus (Vassallo et al 2001), and fibronectin is also bound by the major surface glycoprotein ( previously termed gp120) of P. jirovecii (Pottratz et al 1991).…”
Section: Pnemocystis Jiroveciimentioning
confidence: 99%